Effect of Washed Microbiota Transplantation on Patients With Dyslipidemia in South China - Liang, Fenfen; Lu, Xinjian; Deng, Zhiliang; Zhong, Hao-Jie; Zhang, Wei; Li, Qing; Zhou, Hong-Hao; Liou, Yu-Ligh; He, Xing-Xiang (Frontiers in Endocrinology, 2022)
Background and aims: Although fecal microbiota transplantation (FMT) has been proved to reduce blood lipids in animal models of hyperlipidemia, its clinical effect on blood lipid metabolism in patients with hyperlipidemia and hypolipidemia is still unclear, especially in the Chinese population. The purpose of this study was to investigate the feasibility and effectiveness of washing microbiota transplantation (WMT) on lipid metabolism in the Chinese population. Methods: The clinical data of patients with various indications who received WMT for 2-4 treatment procedures were collected. The changes of blood lipids before and after WMT in patients, including total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), homeostasis model assessment of insulin resistance (HOMA–IR), liver fat attenuation, liver stiffness measurement, were compared. Results: A total of 177 patients (40 cases of hyperlipidemia, 87 cases of normal, and 50 cases of hypolipidemia) were enrolled in the First Affiliated Hospital of Guangdong Pharmaceutical University. WMT has a significant therapeutic effect of reducing blood lipid levels (TC and TG) in the short and medium-term in patients with hyperlipidemia (p <0.05). 35.14% hyper blood lipid decreased to normal in short-term (P<0.001) and 33.33% changed to normal in the medium-term (P=0.013). In the hypolipidemia group, 36.36 % and 47.06% changed to normal in the short-term (P=0.006) and medium-term (P=0.005). In the normal blood lipid group and a low-risk group of ASCVD, the change was not statistically significant indicating that WMT does not increase the risk of blood lipid and ASCVD in long term. Conclusions: WMT treatment has an effect on blood lipid in patients with hyperlipidemia and hypolipidemia. Therefore, the regulation of gut microbiota by WMT may indicate a new clinical method for the treatment of dyslipidemia.